PENGEMBANGAN BAHAN AJAR MENGGUNAKAN MODEL RME PADA TEMA 2 (SELALU BERHEMAT ENERGI) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS 4 SD SWASTA MIS AL-HIDAYAH - Ahmad Landong; Adinda Febriany Br Sembiring; Ananda Azzahra Sp; Arum Sasri Wilujeng; Rizki Rahmadani Pohan; Septi Novita Panjaitan; Siti Hazizah Br Barus; Sri Wahyuni; Tiara Puspita Sari; Widia Amalia Arfa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop teaching materials using the RME model in theme 2 (Always Save Energy) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) approach to improve the critical thinking skills of 4th grade students at MIS Al-Hidayah Private Elementary School. The research method used is Research and Development (R&D). Based on the validation results, the teaching materials developed were declared valid and suitable for use. Media experts provide a "Valid" assessment of teaching materials using the RME model. Teacher assessment also shows that the teaching materials meet the validity criteria. The research results also show that the curriculum used in schools is the 2013 Curriculum with learning methods that include lectures, questions and answers, and discussions. The conclusion of this research is that teaching materials using the RME model can improve the critical thinking skills of grade 4 students at MIS Al-Hidayah Private Elementary School and are suitable for use in learning.